FUNGSI KOMUNIKASI DAKWAH DI ERA MULTI MEDIA - Suharto Suharto (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
This article examines the function of preaching communication in the multimedia era. Preaching communication that is increasingly developing is no longer through conventional media with communication strategies that still rely on face-to-face or stagnant in one mass media. Especially regarding propaganda material that contains inviting, educating or informing facts or something that is considered to be beneficial to the Ummah, the preachers have been more effective and practical in disseminating quickly through social media, the religious teachers can disseminate propaganda content in WhatsApp Group or WAG, messenger, instagram, can also be through other networked media.